Evaluation of Nutricional status in type 2 Diabetic Patients and Malnutrition (Boletin Médico de Postgrado, 2017)
In the approach to Type 2 Diabetes Mellitus one of the fundamental pillars is the evaluation of the nutritional status of the patient, generally this group of chronic diseases is associated with nutritional alterations due to a decrease in energy reserves and an inadequate intake of nutrients Which negatively impacts on the integral management of this pathology and its comorbidities. The present study aimed to correlate parameters of anthropometric evaluation and serum protein levels in patients with Type 2 Diabetes Mellitus and malnutrition hospitalized in the Internal Medicine Services of the Central University Hospital Dr. Antonio María Pineda. The type of work was observational or what is the same non-experimental, transversal of cases and controls, retrospective. The sample consisted of 30 diabetic malnourished type 2 diabetic patients and 15 healthy individuals, who underwent quantification of BMI, mean arm circumference, tricipital fold, subscapular fold, percentage of fat area and muscle area, and quantification of The total and fractionated proteins. It was evidenced that the group of diabetics had lower anthropometric and biochemical parameters than healthy ones. In turn, it was observed that more than 90% of diabetics and about 60% of healthy individuals had deficits in the fat and muscle area, despite having protein and BMI within normal. There was no statistical correlation between the anthropometric and biochemical parameters. It is concluded that in spite of not having correlation, the inclusion of the skin folds within the evaluation of the patient are indispensable elements to provide an adequate nutritional diagnosis.
Keywords: Type 2 diabetes mellitus; Undernourished; Anthropmetry; Serum protein